2013
DOI: 10.1242/jcs.122119
|View full text |Cite
|
Sign up to set email alerts
|

PfSec13 is an unusual chromatin associated nucleoporin of Plasmodium falciparum, which is essential for parasite proliferation in human erythrocytes

Abstract: SummaryIn Plasmodium falciparum, the deadliest form of human malaria, the nuclear periphery has drawn much attention due to its role as a subnuclear compartment involved in virulence gene expression. Recent data have implicated components of the nuclear envelope in regulating gene expression in several eukaryotes. Special attention has been given to nucleoporins that compose the nuclear pore complex (NPC). However, very little is known about components of the nuclear envelope in Plasmodium parasites. Here we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 89 publications
0
77
0
Order By: Relevance
“…9A; Supplemental Table 6), providing independent support for the clustering of VRSM genes. Although previous FISH results indicated that var genes form two to five clusters in 3D per cell (Freitas-Junior et al 2000;Lopez-Rubio et al 2009), others recently showed single foci for the VRSM gene-associated repressive histone mark H3K9me3 and heterochromatin protein 1 (PfHP1) (Dahan-Pasternak et al 2013), as well as for H3K36me3 that marks both active and silenced var genes (Ukaegbu et al 2014). Because our experimental strategy (Hi-C) captures a population average, we are unable to distinguish between multiple VRSM gene clusters in 3D if the genes are randomly distributed among clusters from cell to cell.…”
Section: Virulence Gene Clusters On Different Chromosomes Colocalize mentioning
confidence: 99%
“…9A; Supplemental Table 6), providing independent support for the clustering of VRSM genes. Although previous FISH results indicated that var genes form two to five clusters in 3D per cell (Freitas-Junior et al 2000;Lopez-Rubio et al 2009), others recently showed single foci for the VRSM gene-associated repressive histone mark H3K9me3 and heterochromatin protein 1 (PfHP1) (Dahan-Pasternak et al 2013), as well as for H3K36me3 that marks both active and silenced var genes (Ukaegbu et al 2014). Because our experimental strategy (Hi-C) captures a population average, we are unable to distinguish between multiple VRSM gene clusters in 3D if the genes are randomly distributed among clusters from cell to cell.…”
Section: Virulence Gene Clusters On Different Chromosomes Colocalize mentioning
confidence: 99%
“…The same catalytic activity is lacking in another flagellated excavate Giardia lamblia, 4 and autoproteolytic cleavage has been shown to be dispensable for cell growth in fission yeast. 26 Additionally, the Apicomplexan parasite Plasmodium falciparum has an unusual fusion of a portion of the a solenoid domain of this protein (ScNup145C) with PfSec 13 27 . Thus, trypanosomes do not represent the exception -instead, they are part of the rule that the outer ring complex (comprising one-third of the NPC's mass) can apparently vary considerably in form and function between different organisms.…”
Section: Copy and Paste: The Npc's Scaffold Arose Through Ancient Dupmentioning
confidence: 99%
“…The first group of ten compounds was substituted with chlorine in para position of the phenoxy residue, like in the scaffold of TCMDC-137332 (1-10). Another equivalent series was synthesized, in which the chlorine was replaced by a more polar methoxy group (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). …”
Section: Chemistrymentioning
confidence: 99%
“…The derivatives 1-20 were examined in 3µM concentration performing viability assays measuring the bioluminescence in a luciferase assay system as described earlier [17][18][19][20]. A first screening, in which the cultures were incubated for 48 h, gave surprisingly low inhibition rates of the parasite growth (see Figure 3).…”
Section: In Vitro Assaymentioning
confidence: 99%